2022
DOI: 10.3390/agronomy12030665
|View full text |Cite
|
Sign up to set email alerts
|

Cellulolytic Properties of a Potentially Lignocellulose-Degrading Bacillus sp. 8E1A Strain Isolated from Bulk Soil

Abstract: Cellulolytic enzymes produced by spore-forming bacteria seem to be a potential solution to the degradation of lignocellulosic waste. In this study, several dozen bacterial spore-forming strains were isolated from soil and one of them was selected for further studies. The studied bacterial strain was identified to genus Bacillus (strain 8E1A) by 16S rRNA gene sequencing. Bacillus sp. 8E1A showed an activity of carboxymethyl cellulase (CMCase) with visualization with Congo Red-25 mm (size of clear zone). To stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…Mechanisms of direct action include production of various biological substances, for instance, indole-3-acetic acid (IAA), gibberellins, cytokinins, and 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase, and atmospheric nitrogen fixation (nitrogenase production), or phosphorus solubilization [ 56 , 108 , 109 , 110 , 111 , 112 ]. On the other hand, indirect mechanisms include the production of antibiotics (for example, cyclic lipopeptides), enzymes such as chitinases, cellulases, and glucanases, and siderophore production [ 105 , 113 , 114 , 115 , 116 ].…”
Section: Heavy Metal Bioremediation Strategies Detected In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms of direct action include production of various biological substances, for instance, indole-3-acetic acid (IAA), gibberellins, cytokinins, and 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase, and atmospheric nitrogen fixation (nitrogenase production), or phosphorus solubilization [ 56 , 108 , 109 , 110 , 111 , 112 ]. On the other hand, indirect mechanisms include the production of antibiotics (for example, cyclic lipopeptides), enzymes such as chitinases, cellulases, and glucanases, and siderophore production [ 105 , 113 , 114 , 115 , 116 ].…”
Section: Heavy Metal Bioremediation Strategies Detected In ...mentioning
confidence: 99%
“…Importantly, by conducting research on the PGPB application for bioremediation of heavy metals under controlled conditions, researchers are reducing the number of factors affecting their effectiveness. As is well known, the effectiveness of PGPB is influenced by soil properties (including chemical and microbiological properties), which are modulated by a range of factors including meteorological conditions [ 116 ]. Thereby, there is still a great need for research conducted under field conditions, which will provide a broader view of the interactions between bacteria, plants, and soil, thus leading to an essential step in the transition from laboratory experiments to practical applications.…”
Section: Heavy Metal Bioremediation Strategies Detected In ...mentioning
confidence: 99%
“…Using a laccase treatment, the authors of [58] decreased the phenolic compound concentration in hemp straw and significantly lowered (p < 0.05) the inhibition levels for biogas production. A new, interesting direction of studies on microbial inoculants for the preservation of green biomass is the selection of microorganisms with specific enzyme activities [59].…”
Section: Discussionmentioning
confidence: 99%
“…Soil from different environments can serve as a source of cellulolytic microorganisms. A number of studies focused on the isolation of single strains from various soil types [ 14 , 15 , 16 , 17 , 18 ], but this approach has several flaws. It was reported that cellulolytic bacteria may take up to a fifth of the total soil community [ 19 ].…”
Section: Introductionmentioning
confidence: 99%